PENGARUH INSIDER OWNERSHIP TERHADAP DIVIDEND PAYOUT RATIO DENGAN MEDIASI DEBT TO EQUITY RATIO (Studi pada Industri Manufaktur di Bursa Efek Indonesia Periode Tahun 2008 - 2010) - Ig. Hery Sedewo, 11.42.02.0039 (Students Journal of Accounting and Banking, 2013)
This study is performed to examine the effect of debt to equity ratio (DER) and Insider ownership toward Dividend Payout Ratio (DPR) in companies that is listed in BEI. The objective of this study is to scale and analyze the effect of the company financial ratios performance (DER, and Insider ownership) toward DPR in companies that is listed in BEI over period 2008-2010. Sampling technique used here is purposive sampling on criterion (1) the company that trade their stocks in Indonesian Stock Exchange; (2) the company having insider ownership per December 2008-2010; and (3) the company that continually share their dividend per December 2008-2010. The data is obtained based on Indonesian Capital Market Directory (ICMD 2011) publication. It is gained sample amount of 69 companies from 153 companies those are listed in BEI. The analysis technique used here is multiple regression with the least square difference and hypothesis test using t-statistic to examine partial regression coefficient and f-statistic to examine the mean of mutual effect with level of significance 5%. In addition, classical assumption is also performed including normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. During 2008-2010 period show as deviation has not founded this indicate clasiccal assumption that the available data has fulfill the condition to use multi linier regression model. Empirical evidence show insider ownership to have influence toward DER at level of significance less than 5%, insider ownership have not influence toward DPR at level of significance more than 5%, and DER to have influence toward DER at level of significance less than 5%, Keywords: debt to equity ratio (DER) Insider ownership, and Dividend Payout Ratio (DPR)